Preceding bortezomib administration for a certain period reduces the risk of lenalidomide‐induced skin rash - Sugi, Tomiyuki; Mita, Mitsuo; Yasu, Takeo; Kubo, Kana; Kushi, Ryota; Hanai, Homare; Ohara, Shin; Uchida, Tomoyuki; Inoue, Morihiro; Hagihara, Masao (Journal of Clinical Pharmacy and Therapeutics, 2022)
What is known and objective It was previously reported that the incidence of lenalidomide (LEN)‐induced skin rash is reduced by administration of bortezomib (BOR) prior to LEN administration in patients with multiple myeloma (MM). Therefore, we investigated whether LEN‐induced skin rash is affected by the duration of BOR administration and the dosing interval between BOR and LEN administration. Method A retrospective investigation was conducted among MM patients who received BOR treatment prior to LEN treatment in Eiju General Hospital from May 2010 to December 2020. We investigated whether the BOR administration duration and interval duration from the completion of BOR administration to the initial LEN administration affect the development of LEN‐induced skin rash. Result and discussion Twenty‐eight of the 81 patients exhibited LEN‐induced skin rash (34.6%). The administered duration, but not the interval, was significantly longer in the group without skin rash. Cut‐off values were set for the duration of administration and interval, which were 35 days and 30 days, respectively. Multivariate analysis was performed on patients which are administered duration of more than 35 days and intervals of less than 30 days, and those who are not applicable. A significant difference was observed in the incidence of skin rash for each factor. What is new and conclusion The risk of reduced LEN‐induced skin rash is affected not only by the presence of prior BOR administration, but also by the duration of BOR and the interval from the completion of BOR to the initial LEN administration. Differences in the bortezomib administration period before the initial lenalidomide administration and the interval period from the final bortezomib administration to the initial lenalidomide administration affect the incidence of lenalidomide‐induced skin rash.